Mirror-mirror on the wall, what psychological effects of COVID-19 and strategies practiced can prevent deterioration of mental health by Malaysian of all? - Choe, Chai Tan; Zakaria, Noor Syamilah; Mohamad Yusop, Yusni; Abdrahim, Nur Aira (HRMARS, 2021)
On a daily basis, the number of global COVID-19 cases is increasing rapidly. In Malaysia, the number of confirmed cases surged after the September 2020 Sabah state election. This caused the government and the Ministry of Health to issue warnings and to once again impose restrictions of movement. Many Malaysians who had gone through the strict Movement Control Orders (MCOs) imposed since March 2020 had to face the psychological effects of the consequent economic recession once again and adapt to their new daily routines under the MCOs. With new increases in the numbers of confirmed cases, the level of anxiety has risen sharply, especially the uncertainty of when the threat of COVID-19 will be lessened. It is pertinent to explore both the psychological and emotional impact to find ways to reduce the stress and effectively address the mental health issues arising from this pandemic. This paper focuses on the causes of uncertainties faced by Malaysians and the strategies employed to overcome these effects. Essentially, there are internal and external methods which can be a guide to individuals to help them develop better coping skills in this anxious situation. Individuals should be aware of their emotional state and practise self-care to prevent a decline of their mental health.